Predictors of reading comprehension and profiling of poor readers in Croatian: educational and clinical perspectives - Kuvač Kraljević, Jelena; Runje, Nikolina; Ružić, Valentina; Škorić, Ana Matić; Lenček, Mirjana; Štefanec, Antonia (Frontiers in Psychology, 2024)
Introduction: Reading is an important academic skill. Children who exhibit reading difficulties are more likely to experience various negative professional and personal consequences. To successfully identify children with reading problems as early as possible, one must first understand how reading skills can be mastered, as well as the course of reading development in children with typical reading skills from the beginning of their formal reading instruction. Thus, the purpose of this study was to determine the influence of decoding and language comprehension on reading comprehension ability. In addition, this study aimed to determine types of profiles among poor readers and estimate their frequency in the study sample. Method: Based on the Simple View of Reading model, we developed decoding, language comprehension, and reading comprehension tasks. Participants included 100 typical readers (TR) and 95 poor readers (PR) in the second grade in Croatian schools. Phonemic awareness, phonological working memory, and rapid automatized naming tasks were used to test underlying abilities of decoding skills in both groups of participants. Results: As expected, PRs showed significantly lower performance on all variables than TRs. The correlations between decoding, language comprehension and reading comprehension are significant in the PR group. The linear regression analysis showed that language comprehension was a significant predictor of reading comprehension for TRs, while decoding and language comprehension were significant predictors of reading comprehension for PRs. The profiling of reading difficulties revealed five different profiles, the most common of which was a mixed reading difficulty, i.e., difficulties in both decoding and language comprehension. Discussion: In line with theoretical expectations, success in reading comprehension in TRs at the end of the second grade depends mainly on language comprehension. To achieve this complex cognitive skill, PRs` language comprehension alone is not sufficient, so they still rely on their decoding skills. Among the poor readers, there was a high prevalence of children with decoding problems (i.e., three out of five profiles). Teachers should be able to identify and monitor decoding difficulties in children, since these difficulties are associated with noticeable manifestations, unlike those associated with comprehension difficulties.